E-blackboard Från krittavla till webbgr änssnitt - Andersson, Simon; Botonjic, Saudin; Lundgren, Christoffer; Parviainen, Dennis; Selldén, Tomas (My University, 2014)
This bachelor thesis covers the development of a semi-autonomous system which helps students by electronically providing information presented on blackboards during a lecture. The system consists of a camera module connected to a Raspberry Pi mounted on a rotating frame, which enables the system to cover all of the boards in the lecture hall. The frame's rotation is controlled by a servo-engine connected to the Raspberry Pi. Images captured by the system are automatically processed on the Raspberry Pi through the use of the graphics framework SimpleCV in a python script. The images are published on an online interface where students can access them and rehearse the content covered during the lecture. The project ultimately resulted in a prototype where an image is presented on the online interface approximately 40 seconds after a blackboard has been completed. This delay is considered acceptable since a board rarely has to be documented more frequently. The automatic image processing will correct the perspective as needed and crop the image to exclude any unnecessary information before publishing the image on the online interface. The system requires minimal interaction from the lecturer. This consists of moving the blackboard to the highest position of the board's frame. The overall result of this project indicates that a system with this type of functionality can be implemented and is likely to have a positive impact on students' learning.
Keywords: Data- och informationsvetenskap; Computer and Information Science